Living with Disputes: Zhang Gang Diary (1888–1942) and the Life of a Community Mediator in Late Qing and Republican China - Guo, Weiting (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2013)
Using a newly available personal journal, Zhang Gang Diary (1888–1942), this study explores an understudied area of Chinese legal history: the everyday practice of community mediators in the late Qing and Republican eras. The records of the Zhang Gang Diary reveal how social, political, and judicial transformations impacted the practice of local mediation during a period of significant political and cultural change. The community mediator of this generation had increasingly limited room for mediation. However, as the diary reveals, community mediators also swiftly adapted to the new changes. Through a close reading of the life history of one village mediator, this paper examines a relatively low-status gentleman’s strategy for survival and how he responded to the grand societal and political transformations of late Qing and Republican China.